2019
DOI: 10.1039/c9bm00957d
|View full text |Cite
|
Sign up to set email alerts
|

Polymer design and component selection contribute to uptake, distribution & trafficking behaviours of polyethylene glycol hyperbranched polymers in live MDA-MB-468 breast cancer cells

Abstract: Properties of hyperbranched polymer surface chemistry control cellular distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…Its magnetic core makes it possible for utilization in the diagnosis as it is detected by MRI on injection to tissues. On one side, where Poly-L-glutamic acid (PLGA; a synthetic biodegradable polymer) is employed for conjugate synthesis, polyethylene glycol (PEG) and N-(2-hydroxypropyl)-methacryl amide copolymer (HPMA) are the most widely used non-biodegradable polymers of synthetic origin [40][41][42][43]. PLGA (Poly-(lactic-co-glycolic acid) nanoencapsulated with Callistemon citrinus phenolics exhibited anticancer properties against BC cell lines viz.…”
Section: Polymeric-based Nanoparticlesmentioning
confidence: 99%
“…Its magnetic core makes it possible for utilization in the diagnosis as it is detected by MRI on injection to tissues. On one side, where Poly-L-glutamic acid (PLGA; a synthetic biodegradable polymer) is employed for conjugate synthesis, polyethylene glycol (PEG) and N-(2-hydroxypropyl)-methacryl amide copolymer (HPMA) are the most widely used non-biodegradable polymers of synthetic origin [40][41][42][43]. PLGA (Poly-(lactic-co-glycolic acid) nanoencapsulated with Callistemon citrinus phenolics exhibited anticancer properties against BC cell lines viz.…”
Section: Polymeric-based Nanoparticlesmentioning
confidence: 99%
“…On the other hand, if designed carefully, this interaction can also be exploited, for example, for the accumulation in specific cell organelles. [74,75] Furthermore, such polymeric nano-theranostics allow for real-time monitoring of nanomedicine interventions, enhancing personalized medicine approaches, and providing clinicians otherwise unavailable information for predicting patient outcomes at the earliest possible time. Such combination approaches afforded by nanomedicines are at the forefront of next-generation nanomedicines being developed, and the authors expect these to have a significant impact in future clinical outcomes, especially in difficult-to-treat malignancies with currently poor clinical outcomes.…”
Section: Theranostics-combining Therapeutics and Diagnosticsmentioning
confidence: 99%
“…On the other hand, if designed carefully, this interaction can also be exploited, for example, for the accumulation in specific cell organelles. [ 74,75 ]…”
Section: Theranostics—combining Therapeutics and Diagnosticsmentioning
confidence: 99%
“…58 Or, appending biologically relevant groups on SHP linear segments can endow the SHP with significant therapeutic potential. In this regard, the Thurecht group has pioneered an impressive range of potential applications for biologically relevant SHPs, 50,51,[59][60][61][62][63][64][65][66][67][68][69][70][71][72] including fluorine-labeled SHPs for 19 F magnetic resonance imaging, 63,67,73 hyperpolarized SHPs that could enhance traditional magnetic resonance imaging 72 and SHP delivery vehicles for peptides and nucleic acids. 51,59,60,69 Appel and coworkers also very recently demonstrated that targeting low primary chain degrees of polymerization enables extensive decoration of SHPs with functional chain ends.…”
Section: Synthesis Of Functional Shpsmentioning
confidence: 99%